(untitled) (CIPEEX, 2025)
This study aims to analyze the concept, foundations, purpose, and scope of the Police Power, as well as its main characteristics. The analysis is based on the doctrine presented in FILHO, José dos Santos C., Manual de Direito Administrativo, 38th Edition, 2024. Police Power can be defined as the State’s legal authority to impose limitations on individual freedoms and property use, in order to protect collective interests, public order, health, the environment, and social welfare. It is grounded in the principle of the supremacy of public interest, allowing the State to intervene in individual rights to safeguard the community. Police Power encompasses multiple dimensions — material, moral, cultural, environmental — and prioritizes collective over individual interests, covering areas such as construction, health, and traffic regulation. Its main characteristics include discretion, enabling the administration to act based on convenience and opportunity; self-executing authority, allowing immediate action without judicial approval; and coercibility, ensuring compliance with decisions regardless of individual consent. The study concludes that Police Power is essential for protecting collective interests by balancing individual rights and social welfare.